Subcascade formation and defect cluster size scaling in high-energy collision events in metals. (17th August 2016) - De Backer, A.; Sand, A. E.; Nordlund, K.; Luneville, L.; Simeone, D.; Dudarev, S. L.
Abstract: It has been recently established that the size of the defects created under ion irradiation follows a scaling law (Sand A. E. et al., EPL, 103 (2013) 46003; Yi X. et al., EPL, 110 (2015) 36001). A critical constraint associated with its application to phenomena occurring over a broad range of irradiation conditions is the limitation on the energy of incident particles. Incident neutrons or ions, with energies exceeding a certain energy threshold, produce a complex hierarchy of collision subcascade events, which impedes the use of the defect cluster size scaling law derived for an individual low-energy cascade. By analyzing the statistics of subcascade sizes and energies, we show that defect clustering above threshold energies can be described by a product of two scaling laws, one for the sizes of subcascades and the other for the sizes of defect clusters formed in subcascades. The statistics of subcascade sizes exhibits a transition at a threshold energy, where the subcascade morphology changes from a single domain below the energy threshold, to several or many sub-domains above the threshold. The number of sub-domains then increases in proportion to the primary knock-on atom energy. The model has been validated against direct molecular-dynamics simulations and applied to W, Fe, Be, Zr and sixteen other metals, enabling the prediction of full statistics of defect cluster sizes with no limitation on the energy of cascade events. We find that populations of defect clusters produced by the fragmented high-energy cascades are dominated by individual Frenkel pairs and relatively small defect clusters, whereas the lower-energy non-fragmented cascades produce a greater proportion of large defect clusters.